2011
DOI: 10.1148/radiol.11101301
|View full text |Cite
|
Sign up to set email alerts
|

Focal Bone Abnormality as a Complication of Ultrasound Diathermy: A Report of Eight Cases

Abstract: This study demonstrated that ultrasound diathermy may produce an osseous injury. The abnormality itself was usually mild and transient, with apparent full recovery after termination of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Patient 1, on follow-up MR evaluation, demonstrated near complete resolution of bone marrow abnormalities at 13 months after ultrasound diathermy procedure. These results are similar to those of previous observations of resolution of lesions within 12 months [ 4 ]. However, patient 2 had small, residual focal bone marrow lesions in MR examinations taken 5 years after initial visit.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Patient 1, on follow-up MR evaluation, demonstrated near complete resolution of bone marrow abnormalities at 13 months after ultrasound diathermy procedure. These results are similar to those of previous observations of resolution of lesions within 12 months [ 4 ]. However, patient 2 had small, residual focal bone marrow lesions in MR examinations taken 5 years after initial visit.…”
Section: Discussionsupporting
confidence: 93%
“…Review of past literature revealed only one study on focal bone abnormality as a complication of ultrasound diathermy. Yeh et al [ 4 ] described eight patients who developed marrow lesions similar to those of focal osteonecrosis at various joints after undergoing physiotherapy using ultrasound diathermy. Pre-ultrasound diathermy procedure MR image evaluations were not available in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations